ANTIMICROBIAL RESISTANCE: A GLOBAL HEALTH THREAT AND STRATEGIES FOR PREVENTION - Kamoljonova Go‘zaloy Odiljon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Antimicrobial resistance (AMR) has emerged as one of the most significant public health threats of the 21st century. The misuse and overuse of antibiotics, combined with the lack of new antimicrobial agents, has accelerated the evolution of resistant pathogens. This article explores the global burden of AMR, outlines contributing factors, and examines current and emerging strategies for prevention.